108 Attentional Control Deficits during Total Sleep Deprivation: Independence from Reduced Vigilant Attention. (3rd May 2021) - Lawrence-Sidebottom, Darian; Hinson, John; Whitney, Paul; Honn, Kimberly; Van Dongen, Hans
Abstract: Introduction: Total sleep deprivation (TSD) has been shown to impair performance on a two-phase attentional control task, the AX-type continuous performance task with switch (AX-CPTs). Here we investigate whether the observed AX-CPTs impairments are a downstream consequence of TSD-induced non-specific effects (e.g., reduced vigilant attention) or reflect a distinct impact on attentional control. Methods: N=55 healthy adults (aged 26.0±0.7y; 32 women) participated in a 4-day laboratory study with 10h baseline sleep (22:00-08:00) followed by 38h TSD and then 10h recovery sleep. At baseline (09:00 day 2) and after 25h and 30h TSD (09:00 and 14:00 day 3), subjects were tested on a 10min psychomotor vigilance test (PVT), an assay of vigilant attention, and on the AX-CPTs. The AX-CPTs required subjects to differentiate designated target from non-target cue-probe pairs. In phase 1, target trials occurred frequently, which promoted prepotent anticipatory responses; in phase 2, the target pair was switched. Accuracy of responses to various different AX-CPTs trial types was expressed relative to accuracy on phase 1 neutral (non-target cue and probe) trials, which should capture non-specific impairments on the task. For all three test sessions, these relative accuracy measures, along with accuracy on phase 1 neutral trials and lapses (RT>500ms) on the PVT, were subjected to principal component analysis (PCA). Results: The PCA revealed three statistically independent factors. Following varimax rotation, factor 1 (36.3% variance explained) and factor 3 (14.8% variance explained) each had high loadings for relative accuracy on multiple AX-CPTs trial types from phases 1 and 2; whereas factor 2 (17.9% variance explained) had high loadings for accuracy on phase 1 neutral trials, relative accuracy on phase 1 target trials, and PVT lapses. Conclusion: These results indicate a statistical separation between AX-CPTs phase 1 neutral trials and phase 1 target trials, in conjunction with PVT lapses, versus the various other AX-CPTs trial types. This suggests a dissociation between TSD-induced, non-specific impairments on the task—potentially related to reduced vigilant attention—and TSD-induced specific impairments related to attentional control. Thus, TSD-induced deficits in attentional control are unlikely to be a downstream consequence of non-specific impairments. Support (if any): CDMRP grant W81XWH-16-1-0319